1990
DOI: 10.1071/rj9900007
|View full text |Cite
|
Sign up to set email alerts
|

Intake of lick block supplements by cattle grazing native monsoonal tallgrass pastures in the Northern Territory.

Abstract: Four supplementation treatments to investigate wet seasons responses were imposed on eight Brahman/Shorthom cross herds totalling 870 animals of all classes (cows and calves, bulls, heifers and steers). They grazed 12,300 ha of native pasture in the Darwin district of the Northern Territory. The treatments were: (i) control (no wet season supplement), (ii) Mineral (Ultraphos - supplementation with 13 minerals during the wet season), (iii) +Protein (Ultrapro-50 - the same 13 minerals plus non-protein nitrogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…As expected, supplementation with non-protein nitrogen to cattle grazing low quality tropical pastures had a remarkable response on body weight and shifted the rumen fermentation profile. The ADWG of the supplemented pregnant heifers increased over 0.500 kg per day, which is greater than that in previous published studies [ 2 , 9 , 10 , 11 , 39 , 45 ]. However, these studies reported a less acute loss of weight, maintenance, or increases up to 0.300 kg per day in cattle supplemented with urea and other micronutrients (e.g., sulfur) during the dry season.…”
Section: Discussioncontrasting
confidence: 57%
“…As expected, supplementation with non-protein nitrogen to cattle grazing low quality tropical pastures had a remarkable response on body weight and shifted the rumen fermentation profile. The ADWG of the supplemented pregnant heifers increased over 0.500 kg per day, which is greater than that in previous published studies [ 2 , 9 , 10 , 11 , 39 , 45 ]. However, these studies reported a less acute loss of weight, maintenance, or increases up to 0.300 kg per day in cattle supplemented with urea and other micronutrients (e.g., sulfur) during the dry season.…”
Section: Discussioncontrasting
confidence: 57%
“…Many animals may not consume any supplement, while among those that do consume there may be high variability in supplement intake (Arnold and Maller 1974;Nolan et al 1975;Murray et al 1978;Eggington et al 1990;Bowman and Sowell 1997). Variability in intake of supplements is likely to be particularly high when mineral and non-protein nitrogen supplements are provided ad libitum as loose mineral mix or solidified feed blocks to grazing animals (Dixon and Petherick 1996;Dixon and Smith 2000;Dixon et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In another study dealing with molasses blocks (Graham et al 1977) the consumed amount varied between 0 and 387 g·day -1 . Eggington et al (1990) found even bigger variation -they described the range in acceptance of salt block between 10 g and 835 g·day -1 . Apart from variations in the amount of lick intake, there were variations in the acceptance of molasses blocks (of identical composition) made by different manufacturers (Ducker et al 1981;Kendall et al 1983).…”
Section: Resultsmentioning
confidence: 99%